Az archaikus költészet szerepe Ioachimus Vadianus költészetelméletében - Bobay Orsolya (Antikvitás és reneszánsz, 2018)
The aim of my study is the analysis of the views on the archaic Latin literature in the early modern works based on the theory and practice of poetry, especially in the Swiss humanist’s, Joachim von Watt’s work (De poetica et carminis ratione). The concepts of poeta vates, poeta theologus, and poeta eruditus are commonly used by the Italian authors – who knew the most important authors of the early Roman literature regarding this period ‒ in order to emphasize the moralistic and social morals of the archaic poetry’s lecture. Some of the authors – for example Pietro Crinito ‒ following Suetonius emphasized the historical analysis of the ancient literature in a particular way. The innovation of Joachim von Watt’s work was the adaptation of this view of the Italian authors, and it is not present in the works of other Viennese humanists on poetry in the first half of the 16th century.